Can we address depression in vision rehabilitation settings? Professionals' perspectives on the barriers to integrating problem-solving treatment. Issue 3 (30th January 2018) - Holloway, Edith; Sturrock, Bonnie; Lamoureux, Ecosse; Keeffe, Jill; Hegel, Mark; Casten, Robin; Mellor, David; Rees, Gwyneth
Abstract: Purpose: Low vision rehabilitation (LVR) is a pertinent context for integrating early, evidence-based psychological interventions given the high prevalence of untreated depression in adults with vision impairment. This study aims to identify the perceived barriers and facilitators to staff-delivered telephone-based problem-solving treatment for primary care (PST-PC) offered as an integrated component of LVR. Methods: Qualitative semi-structured interviews, developed using the theoretical domains framework (TDF) and Consolidated Framework for Implementation Research (CFIR), were conducted with 21 LVR professionals and a clinical psychologist involved in the delivery of PST-PC. Barriers and facilitators at the practitioner, client, intervention, and organizational level were identified with thematic analysis using a "theoretical" approach. Results: Prominent barriers were a lack of role recognition for PST-PC practitioners ( n  = 32), unmet client expectation with PST-PC ( n  = 28), dissatisfaction with telephone delivery ( n  = 27), and limited organizational awareness of PST-PC ( n  = 39). Facilitating factors included a recognized need for evidence-based psychological services ( n  = 28), clients experiencing benefits in early sessions ( n  = 38), PST-PC promoting practical skills ( n  = 26), and comprehensive PST-PC training ( n  = 36). Conclusions: PST-PC may provide an accessible early intervention for LVR clients with depressive symptoms. Ongoing practitioner training, clinical support, and screening potential LVR clients for treatment suitability are likely to enhance delivery in this setting. Implications for rehabilitation: Depression is highly prevalent in adults engaged in low vision rehabilitation (LVR) programs, yet few receive support. Clinical guidelines recommend integrated models of care be offered within rehabilitation settings as early intervention for mild to moderate levels of depressive symptoms. Integrated telephone-based problem-solving treatment for primary care (PST-PC) delivered by trained LVR practitioners is a practical, skills-based model that has potential to increase access to an early psychological intervention in LVR clients with depressive symptoms. LVR clients are often older in age, have multiple comorbid health conditions and a significant level of functional disability, requiring flexibility in the delivery of PST-PC and specialized staff training, and support in working with older and more complex clients.